Women's Participation in Decision Making in Indigenous Communities - Nurmirna Sari (Mahogany Journal De Social, 2024)
This study explores women's participation in decision-making within indigenous communities, focusing on the barriers and supportive factors that influence their involvement in governance. By examining several indigenous communities, the research identifies key obstacles such as cultural norms, economic constraints, and gender-based violence, which limit women's roles in decision-making processes. However, the study also highlights the positive impact of education, supportive leadership, and empowerment programs in enhancing women's participation. The findings suggest that while some communities have made significant progress towards gender equality, others continue to face significant challenges. The study calls for more gender-sensitive policies and increased support for women's leadership to foster more inclusive decision-making practices.